MAIT Cell Activation and Functions - Hinks, Timothy S. C.; Zhang, Xia-Wei (Frontiers in Immunology, 2020)
Mucosal associated invariant T (MAIT) cells are striking in their abundance and their strict conservation across 150 million years of mammalian evolution, implying they must fulfil critical immunological function(s). MAIT cells are defined by their expression of a semi-invariant αβ TCR which recognises biosynthetic derivatives of riboflavin synthesis presented on MR1. Initial studies focused on their role in detecting predominantly intracellular bacterial and mycobacterial infections. However, it is now recognised that there are several modes of MAIT cell activation and these are related to activation of distinct transcriptional programmes, each associated with distinct functional roles. In this minireview, we summarise current knowledge from human and animal studies of MAIT cell activation induced 1) in an MR1-TCR dependent manner in the context of inflammatory danger signals and associated with antibacterial host defence; 2) in an MR1-TCR independent manner by the cytokines interleukin(IL)-12 / -15 / -18 and type I interferon, which is associated with antiviral responses; and 3) a recently-described TCR-dependent ‘tissue repair’ programme which is associated with accelerated wound healing in the context of commensal microbiota. Because of this capability for diverse functional responses in diverse immunological contexts, these intriguing cells now appear to be multifunctional effectors central to the interface of innate and adaptive immunity.